Analisis Konsep Maslahat dalam Konsumsi dari sudut pandang Ekonomi Islam pada masyarakat di desa Slawi-wetan - Riska Khajiyah Isnaini; Nurul Wulandari Putri (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The purpose of this research is to see how the concept of maslahat is used for consumption from the perspective of Islamic economics in Slawi-Wetan Village. Maslahat is a principle that prioritizes achieving the good and welfare of society. This principle relates to consumption, encouraging people to prioritize useful needs and avoid consuming too much. To find out the consumption patterns of the local community, the research method used is a qualitative approach by conducting interviews with them. The results show that most people apply the maslahat principle in consumption, although there are some who still prefer to consume. This research shows that people should better understand the concept of maslahat and learn more about it so that their consumption patterns in the village are more in line with Islamic economic principles.